The Statute Law of the State of New York 321 (1881) - (:unkn) unknown (My University, 1881)
Ch. 3, § 9: Prohibited using, attempting to use, or concealing a slungshot, billy, sandclub or metal knuckles, and any dirk. Punishable by imprisonment for up to 1 year and/or a fine up to $500.
Keywords: POSSESSION - NON-GUN ARMS